EFISIENSI WAKTU DAN TEMPERATUR PADA TEKNIK COATING MELALUI PROSES HOT DIP GALVANIZING TERHADAP KUALITAS PELAPISAN - A, Eliana; Wulandari , Puji ; Iskandar, Taufik; Abrina Anggraini, Sinar Perbawani (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2019)
Corrosion is one of the many problems experienced by iron, especially iron which is used for construction in the open field so as to prevent rapid corrosion, the need for iron coating with protective materials in the form of zinc is necessary. The purpose of this study is to determine the time and temperature efficiency of coating quality in the Hot Dip Galvanizing process, but it is still cheap, efficient and durable for a long time, the method is by using Hot Dip Galvanizing or coating with a temperature of 450oC, 455oC, 460oC for 1 minute, 3 minutes and 7 minutes to produce the most optimal layer. The result showed that the optimum coating quality was at a temperature of 460oC for 7 minutes with a thickness of 107 ?m